ENHANCING PROFESSIONAL SKILLS IN TRANSLATION EDUCATION THROUGH A PRAGMATIC FRAMEWORK IN ENGLISH-UZBEK CONTEXTS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article explores the role of the pragmatic approach in enhancing professional skills among translation students, focusing on English-Uzbek language pairs. The study analyzes how pragmatic elements such as context, speech acts, and cultural nuances influence translation quality and accuracy. Through qualitative observations and classroom-based case studies, the research demonstrates that integrating pragmatic competence into translation training fosters deeper cross-cultural understanding, improves the handling of idiomatic expressions, and enhances overall communication effectiveness. The article emphasizes the need for curriculum reform to include pragmatics in translator education and provides practical methods for its implementation. The findings contribute to developing a more holistic approach to translation pedagogy that bridges linguistic accuracy and communicative appropriateness.